Pengaruh Variasi Suhu Sintering Menggunakan Metode Pencampuran Basah - M. Muntamijayati; Suprihatin Suprihatin; Yanti Yulianti; Simon Sembiring (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
The superconducting material BPSCCO-2212 with doping Pb = 0,2 has been synthesized by the wet mixing method. Calculation is caried out at 800 °C for 10 hours. While sintering is done at 825 °C, 830 °C, 835 °C and 840 °C for 20 hours. The synthesis result were characterized by XRD X-Ray Diffraction) and SEM (Scanning Electron Microscopy). The XRD spectrum analysis results that have been processed using celref, show that in general the samples produced have formed the BPSCCO-2212 phase (indicated the presence of Bi-2212 peaks) and have been oriented (indicated the existence of peaks with h = k = 0, l even number). For the calculation result obtanced the highest volume fraction value at 830 °C sintering temperature with a value FV = 66,97 % and the highest degree of orientation at 825 °C with a value of P = 76,54 %. The results of the SEM photo recorder generally show that the crystals formed are oriented.